Energy balance and body composition in sports and exercise - Loucks, A. B. (Journal of Sports Sciences, 2004)
Many athletes, especially female athletes and participants in endurance and aesthetic sports and sports with weight classes, are chronically energy deficient. This energy deficiency impairs performance, growth and health. Reproductive disorders in female athletes are caused by low energy availability (defined as dietary energy intake minus exercise energy expenditure), perhaps specifically by low carbohydrate availability, and not by the stress of exercise. These reproductive disorders can be prevented or reversed by dietary supplementation in compensation for exercise energy expenditure without any moderation of the exercise regimen. Energy balance is not the objective of athletic training. To maximize performance, athletes strive to achieve an optimum sport-specific body size, body composition and mix of energy stores. To pursue these objectives, athletes need to manage fat, protein and carbohydrate balances separately, but it is impractical for athletes to monitor these balances directly, and appetite is not a reliable indicator of their energy and macronutrient needs. To guide their progress, athletes need to eat by discipline and to monitor specific, reliable and practical biomarkers of their objectives. Skinfolds and urinary ketones may be the best biomarkers of fat stores and carbohydrate deficiency, respectively. Research is needed to identify and validate these and other markers.